Biofilms grown in aquatic microcosms affect mercury and selenium accumulation in Daphnia - Semona Issa; Tomasz Maciej Ciesielski; Øyvind Mikkelsen; Sigurd Einum; Veerle L. B. Jaspers (Ecotoxicology, 2020)
Experiments examining mercury (Hg) toxicity in Daphnia are usually conducted in highly standardized conditions that prevent the formation of biofilm. Although such standardization has many advantages, extrapolation of results to natural conditions and inference of ecological effects is challenging. This is especially true since biofilms can accumulate metals/metalloids and play a key role in their transfer to higher trophic level organisms. In this study, we experimentally tested the effects of spontaneously appearing biofilm in Daphnia cultures on accumulation of Hg and its natural antagonist selenium (Se) in Daphnia magna . We added Hg (in the form of mercury (II) chloride) at two concentrations (0.2 µg/L and 2 µg/L) to experimental microcosms and measured the uptake of Hg and Se by D. magna in the presence and absence of biofilm. To test for consistent and replicable results, we ran two identical experimental sets one week apart. Biofilm presence significantly reduced the accumulation of Hg, while increasing the tissue Se content in D. magna , and these findings were reproducible across experimental sets. These findings indicate that highly standardized tests may not be adequate to predict the bioaccumulation and potential toxicity of metals/metalloids under natural conditions.